Life cycle assessment of Nile Tilapia (oreochromis niloticus) farming in Kenyir Lake, Terengganu - Dullah H.; Malek M.A.; Hanafiah M.M. (MDPI, 2023)
carbon footprint; cichlid; environmental impact assessment; farming system; greenhouse gas; guideline; Intergovernmental Panel on Climate Change; life cycle analysis; Comoe River; Kenyir Lake; Malaysia; Terengganu; West Malaysia; Glycine max; Oreochromis niloticus